Face-lift with the use of an aesthetic massage technology: strategy and tactics - Badin, I.; Gozhenko, O.; Zukow, W. (Journal of Education, Health and Sport, 2011)
To date, massage technology can achieve the desired lifting effect, as well as to maintain the lifting effect is achieved by surgical methods. The choice of tactics aesthetic massage must be justified, and the program of lifting individual. One of the main action is the remodeling of the face and necks, which requires adequate stimulation of its physiological capabilities, aimed to recreate the three-dimensional organization and increase water capacity of the main substance of the dermis, the restoration of quality and quantity of fibrous structures, increased proliferative activity of fibroblasts. From the standpoint of achieving the desired result such as the rehabilitation phase of the relief of skin in problem areas of face, neck and neck, simulations of an oval face, the shortfall amount of soft tissue is a major and decisive. Esthetic massage technique proposed by us, based on a combination of different chiropractic techniques: effects on the skin, muscles, ligaments, face and neck, vascular tone, the state of the lymph ducts, reflex points and facial zone. It allows you to potentiate the effects of other methods of rejuvenation and leads to more effective anti-aging complex. Impact on the reflex zones and acupressure points for aesthetic facelift massage lead to: correction distress syndrome, stimulation of metabolic processes, improve sleep, normalization of muscle tone, activation of tissue regeneration, increased hormonal activity. Important components of aesthetic lifting massage - the duration of the sequence of steps, the repetition of massage techniques, combined application with other medical factors - hardware physiotherapy (iontophoresis, dermal mikrolifting, miostimulation, the use of low-energy laser radiation), cosmetic procedures, hormone - replacement and antioxidant therapy, techniques respiration. Conclusions When forming a lifting massage programs are not encouraged to develop long-term scheme of massage for patients with a strong gravitational ptosis and excess skin, with a predominance of large folds, the second chin. The patient should be advised to consult a plastic surgeon, should be encouraged to consistently complete a comprehensive cosmetic and therapeutic programs for patients who insist on quick results, with consultation of patients with exaggerated and inappropriate expectations of the need to emphasize the limitations and possible side effects and complications of procedures. Application of the technique of aesthetic face and neck massage in an anti-age-lifting programs can improve their effectiveness, both through the achievement of local anti-aging effect and improve the overall condition of the patients.